The Utilization of Artificial Intelligence (AI) in the Development of Islamic Cultural Communication Strategies - Pardianto, Pardianto (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2024)
In the digital era, AI has brought significant impacts on various aspects of communication, including in cultural and religious contexts. Islamic cultural communication requires an approach that considers Islamic values and maintains its alignment with the social and cultural context of modern society. This research aims to examine the role of artificial intelligence (AI) in developing Islamic cultural communication strategies. Through a literature review method, this study identifies trends, potentials, and challenges in the use of AI to support the development of effective and contextual communication strategies within Islamic culture. The research findings show that: 1). AI plays a significant role in facilitating the dissemination of Islamic values in the digital era, 2). AI opens up great potential for the development of more dynamic and data-driven Islamic cultural communication strategies, 3). AI serves as a practical implementation in Islamic cultural communication strategies, and 4). the challenge of using AI is related to the potential misuse of data, which could threaten user privacy and conflict with Islamic cultural values